Characterization of the apical bridge barrier formed following amelogenin apexification - Maha M. F. Mounir; Jamila M. A. Farsi; Turki Y. Alhazzazi; Moustafa A. Matar; Azza A. El-Housseiny (BMC, 2018)
Abstract Background Recombinant amelogenin protein (RAP) is reported to induce complete root apex formation in dog model when used as apexification therapy. It also induces pulp regeneration in 85% of the treated group. Thus, the aim of this study was to investigate the nature of the remaining regenerated calcified tissues of the RAP group that showed no pulp regeneration compared to the calcium hydroxide treated group (CH). Methods A total of 240 dogs' open apex root canals were used, after establishment of canals contamination. Canals were cleaned, irrigated, and filled with RAP as an apexification material and compared with CH. Treated teeth were assessed by H&E, trichrome staining, and/or immunohistochemistry technique, at 1, 3, and 6 months. Results A time-dependent increase in the calcified tissue barrier was observed in the apex of the RAP-treated group compared to the CH-treated group. The newly formed dentin in this RAP group was mainly tubular dentin and was functionally attached to the bone by periodontal ligament, while the CH group showed dentin-associated mineralized tissue (DAMT) associated with the newly formed apical barrier. Conclusions Out results suggest that RAP can be used as novel apexification material, resulting in a thickening and strengthening of the canal walls, and achieving apical closure.